Passages adolescents : leurs matérialisations dans les espaces et les temps informels des institutions éducatives - Aurélie Maurin (Conserveries Mémorielles)
The spaces and moments that we call ‘formal’in educational institutions are subjected to rules, norms, functions as well as spatial and temporal attributes. On the other hand, the ‘informal’ designates spaces that are left out of the formal rule, spaces that are not thought through or organized within the educational frame, but that teenagers occupy, thereby conferring new functions and attributes to those spaces left vacant. The effort to understand and delimit those informal times and spaces is as tricky as it might be for a threshold. The two notions are indeed caught up in the inherent paradox of their constitution and their function: separating and binding, closing and opening in the same movement.My reflections are drawing on a clinical study in the realm of adolescence, a notion that is itself paradigmatic of the concept of threshold. I propose to examine how teenagers use and make sense of these informal times and spaces such as hallways, playgrounds, staircases, etc.. through the concepts of threshold and soglitude. This article contends that adolescents choose those places as the privileged moments of materializing rites of passage. We can thus infer that these places are chosen in order to welcome the stages of the construction of their identity.